Integration between asthma and gastroesophageal reflux disease mediated by bronchial hyperreactivity (Research, Society and Development, 2025)
Introduction: Asthma is one of the most prevalent atopic diseases in the world and its connection with gastroesophageal reflux disease (GERD) has become a relevant object of research in the contemporary medical scenario. Objective: The aim of this study was to characterize the pathophysiological mechanisms that integrate asthma and GERD, especially bronchial hyperresponsiveness, by building knowledge based on robust literature reviews. Materials and Methods: This is an integrative literature review on the general clinical characteristics of the pathophysiological correlation between asthma and gastroesophageal reflux disease. The PICO strategy was used to develop the guiding question. In addition, the descriptors “Asthma”; “Gastroesophageal Reflux Disease”; “Pathophysiology” were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The studies show some evidence that corroborates the integration between the pathophysiological mechanisms of the diseases, hypothesizing that there is a feedback loop between the pathologies, where one can provoke and exacerbate the other. In particular, bronchial hyperresponsiveness, the microaspiration theory and the theory of pressure changes resulting from bronchoconstriction are the ones that best support this integration. Conclusion: There is a clear pathophysiological integration between the diseases; however, it has not yet been possible to use this knowledge to establish a propaedeutic consensus to improve the prognosis of asthmatic patients with GERD or vice versa.